Notarial Challenges for Aircraft Deeds: Unlocking the Potential of Aircraft as Collateral - Yahanan, Annalisa; Murzal, Murzal; Turatmiyah, Sri; Si, Tongle (Hasanuddin Law Review, 2024)
A notary is a public official entrusted with the authority to draft legal deeds pertaining to agreements within the scope of private law. However, their ability to fulfill this role is limited when they are unable to draft aircraft mortgage deeds. This study aims to critically evaluate the scope of a notary's authority in preparing aircraft-related deeds and to examine the various forms of legal deeds that have emerged in practice when aircraft are used as collateral in credit agreements. Using a normative legal approach, the research employs statutory analysis, conceptual exploration, and interpretative methods to assess legal materials. The findings reveal that notaries face considerable obstacles in exercising their authority due to the lack of specific regulations on aircraft mortgages, even as the aviation industry continues to grow rapidly. This regulatory void has resulted in the emergence of diverse deed types, such as Deeds of Agreement for the Transfer of Guarantee and Grant of Power of Attorney, Fiduciary Deeds, and Deeds for the Transfer and Guarantee of Power of Attorney. Furthermore, as aircraft, categorized as registered objects, can be classified as immovable property and potentially treated as mortgageable collateral, the establishment of specific regulations governing aircraft mortgages is essential to avoid legal uncertainty and ensure clear regulatory guidance.